Errata: Zootaxa 1012 - E.p., Arruda; Domaneschi, O. (Zootaxa, 2005)
Arruda, E.P. & Domaneschi, O. (2005) New species of Macoma (Bivalvia: Tellinoidea: Tellinidae) from southeastern Brazil, and with description of its gross anatomy. Zootaxa, 1012, 13–22.